2014
DOI: 10.2105/ajph.2013.301642
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Smoking Behavior During Emerging Adulthood: A Longitudinal Analysis of the Effect of Home Smoking Bans

Abstract: Objectives We studied the effect of home smoking bans on transitions in smoking behavior during emerging adulthood. Methods We used latent transition analysis to examine movement between stages of smoking from late adolescence (ages 16–18 years) to young adulthood (ages 18–20 years) and the effect of a home smoking ban on these transitions. We used data from the Minnesota Adolescent Community Cohort study collected in 2004 to 2006. Results Overall, we identified 4 stages of smoking: (1) never smokers, (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 30 publications
1
25
0
3
Order By: Relevance
“…Women are more focused on health protection, which is reflected in their use of safety equipment when doing sport or using means of transport, adjusting their daily regime to their current health condition and protecting themselves against sunshine. This result is in accordance with conclusions of other authors, who ascribe women greater conscientiousness in their attitude to health, which is reflected in their health behavior (Ghanbarzadeh & Mohamadi, 2012;Mathur, Stigler, Erickson, Perry, & Forster, 2014). The last statistically significant gender difference in health behavior appeared in the Positive thinking factor.…”
Section: Discussionsupporting
confidence: 92%
“…Women are more focused on health protection, which is reflected in their use of safety equipment when doing sport or using means of transport, adjusting their daily regime to their current health condition and protecting themselves against sunshine. This result is in accordance with conclusions of other authors, who ascribe women greater conscientiousness in their attitude to health, which is reflected in their health behavior (Ghanbarzadeh & Mohamadi, 2012;Mathur, Stigler, Erickson, Perry, & Forster, 2014). The last statistically significant gender difference in health behavior appeared in the Positive thinking factor.…”
Section: Discussionsupporting
confidence: 92%
“…Home smoking bans significantly reduce SHS exposure among children 209 , and may also lower the likelihood that children of smokers will take up smoking 32 . Unfortunately, approximately 16% of smoking households did not have any restrictions against indoor smoking by 2006–2007 57 , with a similar proportion in 2010–2011 49 and children in these households were still likely be exposed to SHS.…”
Section: Behavioral and Community Strategies To Reduce/eliminate Shs mentioning
confidence: 99%
“…This may be associated with many interrelated factors, including SHS exposure itself 3, 26, 27 , parental modeling 28, 29 , or physical sensitivities to SHS 30 . However, recent studies suggest that SHS in childhood is an independent factor in susceptibility to smoking initiation 31 ; that home smoking bans may delay or prevent smoking initiation among children of smokers 32 ; and, conversely, that SHS exposure may be a mediating factor making adolescent quitting less likely within the context of a smoking family 25 . Thus, childhood SHS exposure may also have indirect impacts on lifetime cardiovascular health by increasing the likelihood that these children will choose to smoke in adolescence and adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…In USA, it was observed that young adults with a home ban during late adolescence were less likely to be smokers and less likely to progress to higher use later (Mathur et al 2014). In Canada, home smoking ban was found to be positively associated with smokers' mental health among Canadian adults, being consistent for daily smokers and occasional smokers (Asbridge et al 2011).…”
Section: Previous Researchmentioning
confidence: 99%